Cover crop benefit bacteria and increase aggregate-associate soil C and N storage - Fontana, Marianela B.; Novelli, Leonardo Esteban; Sterren, María A.; Uhrich, Walter G.; Rondán, Guillermo A.; Barbagelata, Pedro Anibal; Benintende, Silvia M. (Elsevier, 2024)
The aim of this study was to analyze the effect of four crop sequences with different aboveground biomass and crop residue biochemical composition on biological soil variables, fractions of soil organic matter, and soil aggregation. The study was carried out in a long-term experiment under no-till, in the Argentinean Pampas (31°51′ S; 60°32′ W), on an Aquic Argiudoll. The treatments were: i) fertilized soybean monocropping (Syf), ii) winter cover crop (CC)/ fertilized soybean (CC/Syf), iii) N-fertilized winter CC/fertilized soybean (CCN/Syf), and iv) N-fertilized winter CC/fertilized soybean in a crop rotation: CCN/Syf - wheat [Triticum aestivum L.] for grain production/soybean - maize [Zea mays L.] (CCN/Syf rot). Wheat was used as winter CC. Crop residues were sampled in four moments, and were separated into different fractions. Furthermore, crop residue quality was analyzed according to Van Soest (Cellulose, Hemicellulose, Lignin, Non- structural carbohydrates), and %C and %N was also determined. In soil samples obtained at 0–5 cm depth, we determined: soil organic C, total N, particulate organic matter C and N, mineral-associated organic matter C and N, C and N stocks in different aggregate-size classes, microbial biomass C and N (MBC and MBN), fungal and bacterial biomass-C (FBC and BBC), and N released after a 7-d anaerobic incubation. From June to November, Syf exhibited slower decomposition of soybean stems and an increase in the non-identifiable residue biomass. Intensified crop sequences (i.e., with CC) increased MBC (∼38%) and BBC (∼115%), but had no effect on FBC. The BBC was positively correlated with Hemicellulose (r = 0.86, P < 0.001), but negatively associated with lignin (r = −0.84, P < 0.001) and the lignin:N ratio (r = − 0.89, P < 0.001) in the crop residue. The C and N stocks in aggregates >2000 μm were 263% and 227% greater in treatments with CC than Syf, respectively, and correlated with improvements in the MBC and MBN (r = 0.87, P < 0.001 and r = 0.88, P < 0.001, respectively), particularly the BBC. Intensification of crop sequences through the incorporation of CC provided crop residues with a higher availability of easily decomposable C compounds. This enhancement stimulated the soil biota responsible for decomposition, particularly bacteria. Our study highlights the importance of increasing cropping intensity and covering the soil with live vegetation, resulting in a healthier soil.